2016
DOI: 10.1016/j.pmedr.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A voluntary nutrition labeling program in restaurants: Consumer awareness, use of nutrition information, and food selection

Abstract: Health Check (HC) was a voluntary nutrition labeling program developed by the Heart and Stroke Foundation of Canada as a guide to help consumers choose healthy foods. Items meeting nutrient criteria were identified with a HC symbol. This study examined the impact of the program on differences in consumer awareness and use of nutritional information in restaurants. Exit surveys were conducted with 1126 patrons outside four HC and four comparison restaurants in Ontario, Canada (2013). Surveys assessed participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
6
0
6
Order By: Relevance
“…Differences in the settings of studies, such as a restaurant, cafeteria or fast-food outlet, may result in different findings (22) . Although early research regarding menu labelling with symbols showed a significant increase in healthy choices purchased (23)(24)(25)(26) , more recently, with a larger number of studies available, the research suggests that the use of symbols on menus is inconclusive (27) . Therefore, more research is required to determine the effectiveness in various outlets and among different age groups over a longer period.…”
mentioning
confidence: 99%
“…Differences in the settings of studies, such as a restaurant, cafeteria or fast-food outlet, may result in different findings (22) . Although early research regarding menu labelling with symbols showed a significant increase in healthy choices purchased (23)(24)(25)(26) , more recently, with a larger number of studies available, the research suggests that the use of symbols on menus is inconclusive (27) . Therefore, more research is required to determine the effectiveness in various outlets and among different age groups over a longer period.…”
mentioning
confidence: 99%
“…Para White e colaboradores (2016), a implementação deste tipo de rotulagem em cardápios ainda não é investida pelos restaurantes, do ponto de vista dos autores isto ocorre devido ao fato que este tipo de informação não é obrigatória, desta maneira acaba que os proprietários não aderem a tal estratégia (WHITE et al, 2016).…”
Section: Resultsunclassified
“…3,14,15,16,17,18,19,20 A csomagolt élelmiszerek mellett pedig már az éttermi és közétkeztetési szférában is vannak vizsgálatok arra vonatkozóan, hogy a fogyasztók mennyire figyelnek az élelmiszercímkékre. 21,22 Ezek eredménye szerint az ételválasztás során kevesen figyelték a különböző tápanyaginformációkat (pl. fehérje-, zsír-, rost, szénhidráttartalom), amelyek a menzák menüjén, illetve az éttermi étlapokon voltak feltüntetve.…”
Section: Bevezetésunclassified